Diversity, inclusion, and representation in contemporary dramaturgy : case studies from the field - Kelly, Philippa (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Diversity, Inclusion and Representation in Contemporary Dramaturgy offers fresh perspectives on how dramaturgs can support a production beyond rigid disciplinary expectations about what information and ideas are useful and how they should be shared. The sixteen contributors to this volume offer personal windows into dramaturgy practice, encouraging theater practitioners, students, and general theater-lovers to imagine themselves as dramaturgs newly inspired by the encounters and enquiries that are the juice of contemporary theater. Each case study is written by a dramaturg whose body of work explores important issues of race, cultural equity, and culturally-specific practices within a wide range of conventions, venues, and communities. The contributors demonstrate the unique capacity of their craft to straddle the ravine between stage and stalls, intention and impact. By unpacking, in the most up-to-date ways, the central question of "Why this play, at this time, for this audience?," this collection provides valuable insights and dramaturgy tools for scholars and students of Dramaturgy, Directing and Theatre Studies"--
SECTION FOUR Cultural landscapes, past, present, and future -- 12 The stakes of expanding a cultural landscape: dramaturging, adapting, and performing Gao Xinjian's The Other Shore -- 13 Visit to a zoot planet: UCSC suits up in 2017 -- 14 The Dramaturgical Impulse -- or how big is your universe? -- 15 Dethroning Ourselves from the Center
OCLC-licensed vendor bibliographic record.
Keywords: Drama -- Technique; Race in the theater; Minorities in the performing arts; Theater -- Production and direction; PERFORMING ARTS / Theater / Direction & Production; PERFORMING ARTS / Theater / Playwriting; PERFORMING ARTS / Theater / Stagecraft